A Case of Verrucous Carcinoma Treated by Combination of Radiotherapy and Mohs' Chemosurgery - Kozo Kawaguchi; Yuichi Kurihara; Michiaki Akashi; Takeshi Nakahara (Karger Publishers, 2022)
Verrucous carcinoma (VC) is a rare subtype of squamous cell carcinoma. VC is histologically a benign tumor, but it grows significantly and eventually forms a huge mass. Many different treatments are known, but the first-line treatment is surgical resection. VC has strong local infiltration and frequently recurs, making its local control very difficult in unresectable cases. We present a rare case of VC that could be treated with combined radiotherapy and Mohs' chemosurgery, as a new option for unresectable VC.